Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1)
\(\dfrac{0,375-0,3+\dfrac{3}{11}+\dfrac{3}{12}}{-0,625+0,5-\dfrac{5}{11}-\dfrac{5}{12}}+\dfrac{1,5+1-0,75}{2,5+\dfrac{5}{3}-1,25}\)
\(=\dfrac{\dfrac{3}{8}-\dfrac{3}{10}+\dfrac{3}{11}+\dfrac{3}{12}}{-\dfrac{5}{8}+\dfrac{5}{10}-\dfrac{5}{11}-\dfrac{6}{12}}+\dfrac{\dfrac{3}{2}+\dfrac{3}{3}-\dfrac{3}{4}}{\dfrac{5}{2}+\dfrac{5}{3}-\dfrac{5}{4}}\)
\(=\dfrac{3\left(\dfrac{1}{8}-\dfrac{1}{10}+\dfrac{1}{11}+\dfrac{1}{12}\right)}{-5\left(\dfrac{1}{8}-\dfrac{1}{10}+\dfrac{1}{11}+\dfrac{1}{12}\right)}+\dfrac{3\left(\dfrac{1}{2}+\dfrac{1}{3}-\dfrac{1}{4}\right)}{5\left(\dfrac{1}{2}+\dfrac{1}{3}-\dfrac{1}{4}\right)}\)
\(=\dfrac{3}{-5}+\dfrac{3}{5}\)
\(=-\dfrac{3}{5}+\dfrac{3}{5}\)
\(=0\)
a, \(\dfrac{0,75-0,6+\dfrac{3}{7}+\dfrac{3}{13}}{2,72-2,2+\dfrac{11}{7}+\dfrac{11}{13}}\)
= \(\dfrac{\dfrac{3}{4}-\dfrac{3}{5}+\dfrac{3}{7}+\dfrac{3}{13}}{\dfrac{11}{4}-\dfrac{11}{5}+\dfrac{11}{7}+\dfrac{11}{13}}\)
= \(\dfrac{3.\left(\dfrac{1}{4}-\dfrac{1}{5}+\dfrac{1}{7}+\dfrac{1}{13}\right)}{11.\left(\dfrac{1}{4}-\dfrac{1}{5}+\dfrac{1}{7}+\dfrac{1}{13}\right)}\)
= \(\dfrac{3}{11}\)
b. \(\dfrac{0,357-0,3+\dfrac{3}{11}+\dfrac{3}{12}}{0,625-0,5+\dfrac{5}{11}+\dfrac{5}{12}}\)
= \(\dfrac{\dfrac{3}{8}-\dfrac{3}{10}+\dfrac{3}{11}+\dfrac{3}{12}}{\dfrac{5}{8}-\dfrac{5}{10}+\dfrac{5}{11}+\dfrac{5}{12}}\)
= \(\dfrac{3.\left(\dfrac{1}{8}-\dfrac{1}{10}+\dfrac{1}{11}+\dfrac{1}{12}\right)}{5.\left(\dfrac{1}{8}-\dfrac{1}{10}+\dfrac{1}{11}+\dfrac{1}{12}\right)}\)
= \(\dfrac{3}{5}\)
c, \(-\left|-1,5\right|.\left(1\dfrac{1}{3}-2\right)-\left|-\dfrac{2}{3}\right|\)
= \(-1,5.\left(\dfrac{4}{3}-2\right)-\dfrac{2}{3}\)
= \(-1,5.\left(\dfrac{-2}{3}\right)-\dfrac{2}{3}\)
= \(1-\dfrac{2}{3}=\dfrac{1}{3}\)
6:
\(4D=2^2+2^4+...+2^{202}\)
=>3D=2^202-1
hay \(D=\dfrac{2^{202}-1}{3}\)
7: \(=\dfrac{1}{2}\left(\dfrac{2}{3\cdot5}+\dfrac{2}{5\cdot7}+...+\dfrac{2}{97\cdot99}\right)\)
\(=\dfrac{1}{2}\left(\dfrac{1}{3}-\dfrac{1}{5}+\dfrac{1}{5}-\dfrac{1}{7}+...+\dfrac{1}{97}-\dfrac{1}{99}\right)\)
\(=\dfrac{1}{2}\cdot\dfrac{32}{99}=\dfrac{16}{99}\)
a,\(\dfrac{5}{6}+\left(-\dfrac{1}{2}\right)+\dfrac{3}{4}\)
\(=\dfrac{10}{12}+\left(-\dfrac{6}{12}\right)+\dfrac{9}{12}\)
\(=\dfrac{10-6+9}{12}=\dfrac{13}{12}\)
b,\(\left(0,75-\dfrac{1}{3}\right):\dfrac{7}{15}\)
\(=\left(\dfrac{3}{4}-\dfrac{1}{3}\right):\dfrac{7}{15}\)
\(=\left(\dfrac{9}{12}-\dfrac{4}{12}\right):\dfrac{7}{15}\)
\(=\dfrac{5}{12}:\dfrac{7}{15}\)
\(=\dfrac{25}{28}\)
c,\(\dfrac{7}{12}-\dfrac{3}{4}.\dfrac{5}{6}\)
\(=\dfrac{7}{12}-\dfrac{5}{8}\)
\(=\dfrac{14}{24}-\dfrac{15}{24}\)
\(=-\dfrac{1}{24}\)
d,\(\left(2\dfrac{1}{3}+1\dfrac{3}{4}\right).\dfrac{12}{13}\)
\(=\left(\dfrac{7}{3}+\dfrac{7}{4}\right).\dfrac{12}{13}\)
\(=\left(\dfrac{28}{12}+\dfrac{21}{12}\right).\dfrac{12}{13}\)
\(=\dfrac{49}{12}.\dfrac{12}{13}\)
\(=\dfrac{49}{13}\)
a) \(\dfrac{5}{6}+\left(\dfrac{-1}{2}\right)+\dfrac{3}{4}\)
\(=\dfrac{10}{12}-\dfrac{6}{12}+\dfrac{9}{12}\)
\(=\dfrac{13}{12}\)
b) \(\left(0,75-\dfrac{1}{3}\right):\dfrac{7}{15}\)
\(=\left(\dfrac{3}{4}-\dfrac{1}{3}\right).\dfrac{15}{7}\)
\(=\left(\dfrac{9}{12}-\dfrac{4}{12}\right).\dfrac{15}{7}\)
\(=\dfrac{5}{12}.\dfrac{15}{7}\)
\(=\dfrac{25}{28}\)
c) \(\dfrac{7}{12}-\dfrac{3}{4}.\dfrac{5}{6}\)
\(=\dfrac{7}{12}-\dfrac{5}{8}\)
\(=\dfrac{14}{24}-\dfrac{15}{24}\)
\(=\dfrac{-1}{24}\)
d) \(\left(2\dfrac{1}{3}+1\dfrac{3}{4}\right).\dfrac{12}{13}\)
\(=\left(\dfrac{7}{3}+\dfrac{7}{4}\right).\dfrac{12}{13}\)
\(=\left(\dfrac{28}{12}+\dfrac{21}{12}\right).\dfrac{12}{13}\)
\(=\dfrac{49}{12}.\dfrac{12}{13}\)
\(=\dfrac{49}{13}\)
\(=\left(\dfrac{\dfrac{3}{2}+\dfrac{3}{3}-\dfrac{3}{4}}{\dfrac{5}{2}+\dfrac{5}{3}-\dfrac{5}{4}}+\dfrac{3\left(\dfrac{1}{8}-\dfrac{1}{10}+\dfrac{1}{11}+\dfrac{1}{12}\right)}{-5\left(\dfrac{1}{8}-\dfrac{1}{10}+\dfrac{1}{11}+\dfrac{1}{12}\right)}\right)\cdot\dfrac{2005}{1890}+115\)
\(=\left(\dfrac{3}{5}-\dfrac{3}{5}\right)\cdot\dfrac{2005}{1890}+115\)
=115
a) \(2\left(4x-30\right)-3\left(x+5\right)+4\left(x-10\right)=5\left(x+2\right)\)
\(\Leftrightarrow8x-60-3x+15+4x-40=5x+10\)
\(\Leftrightarrow9x-35=5x+10\)
\(\Leftrightarrow9x-5x=10+35\)
\(\Leftrightarrow4x=45\)
\(\Leftrightarrow x=\dfrac{45}{4}=11,25\)
b) \(\dfrac{11}{12}-\left(\dfrac{2}{5}+x\right)=\dfrac{2}{3}\left(6x+1\right)\)
\(\Leftrightarrow\dfrac{11}{12}-\left(\dfrac{2}{5}+x\right)=4x+\dfrac{2}{3}\)
\(\Leftrightarrow\dfrac{31}{60}+x=4x+\dfrac{2}{3}\)
\(\Leftrightarrow\dfrac{31}{60}-\dfrac{2}{3}=4x-x\)
\(\Leftrightarrow3x=\dfrac{1}{60}\)
\(\Leftrightarrow x=\dfrac{1}{180}\)
c) \(\dfrac{7}{3}-\left(2x-\dfrac{1}{3}\right)=\left(-2\dfrac{1}{6}+1\dfrac{1}{2}\right):0,25\)
\(\Leftrightarrow\dfrac{7}{3}-2x+\dfrac{1}{3}=-1\dfrac{2}{3}:\dfrac{1}{4}\)
\(\Leftrightarrow\dfrac{8}{3}-2x=\dfrac{-5}{3}.4\)
\(\Leftrightarrow\dfrac{8}{3}-2x=\dfrac{-20}{3}\)
\(\Leftrightarrow2x=\dfrac{8}{3}+\dfrac{20}{3}\)
\(\Leftrightarrow2x=\dfrac{28}{3}\)
\(\Leftrightarrow x=4\dfrac{2}{3}\)
d) \(0,75+\dfrac{5}{9}:x=5\dfrac{1}{2}\)
\(\Leftrightarrow\dfrac{3}{4}+\dfrac{5}{9}:x=\dfrac{11}{2}\)
\(\Leftrightarrow\dfrac{5}{9}:x=\dfrac{11}{2}-\dfrac{3}{4}\)
\(\Leftrightarrow\dfrac{5}{9}:x=\dfrac{19}{4}\)
\(\Leftrightarrow x=\dfrac{5}{9}:\dfrac{19}{4}\)
\(\Leftrightarrow x=\dfrac{20}{171}\)
Ta có : A=\(\dfrac{0,5+\dfrac{7}{12}-\dfrac{5}{6}}{1-\dfrac{2}{3}+0,75}=\dfrac{\dfrac{1}{2}+\dfrac{7}{12}-\dfrac{5}{6}}{1-\dfrac{2}{3}+\dfrac{3}{4}}=\dfrac{\dfrac{1}{4}}{\dfrac{13}{12}}=\dfrac{13}{48}\)
thanks